Growth characterisics of Garut sheep and its crossbred - Inounu, Ismeth; Mauluddin, D; ., Subandriyo (Indonesian Animal Sciences Society, 2008)
Based on previous study it is agreed that Von Bertalanffy model is the best fitted growth curve model with highest acuracy compared to Gompertz or Logistic models. For that reason in this study Von Bertalanffy model was used to study growth characterisics of Garut sheep and its crossbred. Relative superiority of crossbred sheep compared to Garut sheep in mature size parameter (A) based on Von Bertalanffy model were respectively: M. charolain X Garut = 19.26%; Hair sheep X Garut = 8.08% and MG X HG or HGÂ X MG = 4.22%. While relative superiority of crossbreds compared to Garut in rate of maturing (k) were respectively: MG = -4.91%; HG = -1.34% dan MHG/HMG = 6.05%. Based on its relative superiority mature size parameter (A) and rate of maturing (k) MHG sheep had prospect for more developed due to its performance in term of high mature body weight, faster in reaching standard of slaughter body weight (35 kg) at 440 days, and it is considere as more eficient in biological and economicaly. Key words: Growth Characteristics, Garut Sheep and Crossbreds, Relative Superiority